Prognostic prediction by 18F-FDG-PET/CT parameters in patients with neuroblastoma: a systematic review and meta-analysis - Hu, Ruimin; Zhang, Yan; Liu, Siying; Lee, Pamela; Liu, Chaohong; Liu, Aiguo (Frontiers in Oncology, 2023)
Purpose Neuroblastoma is a solid malignant tumor with high malignancy and high risk for metastasis. The prognosis of neuroblastoma ranges from spontaneous regression to insensitivity to therapies and widespread metastasis. There is a non-invasive, panoramic imaging technique called 18F-flurodeoxyglucose (18F-FDG) positron emission tomography-computed tomography (PET/CT), which can provide both complete anatomical information via CT and extent FDG uptake value in tumors via positron emission detection. PET/CT is a powerful approach to estimate tumoral metabolic activities, and PET/CT parameters have been demonstrated to be associated with the prognosis of various tumors. However, the predictive performance of PET/CT for prognosis of neuroblastoma remains unclear. This meta-analysis aims to assess the predictive values of maximal standardized uptake value (SUVmax), metabolic tumor volume (MTV), and total lesion glycolysis (TLG) for progression-free survival (PFS)，event-free survival (EFS) and overall survival (OS) in neuroblastoma patients. Methods Literatures in PubMed, Embase, Cochrane library, and Web of Science were searched from January 1985 to June 2023 for studies evaluating predictive values of PET/CT parameters for prognosis of neuroblastoma. Search items mainly included “Positron Emission Tomography Computed Tomography” and “Neuroblastoma”. Hazard ratio (HR) were used as pooled statistic to assess the association of SUVmax, MTV, and TLG with PFS, EFS and OS in neuroblastoma patients. Heterogeneity test and sensitivity analysis were performed. Results There were 8 studies included, with 325 participants. Meta-analysis showed that higher SUVmax was associated with shorter OS [HR=1.27, 95% (1.11, 1.45), p=0.001], while no association with PFS [HR=1.03, 95% (0.99, 1.07), p=0.222] and EFS [HR=2.58, 95%(0.37, 18.24), p=0.341] were presented. MTV showed no association with OS [HR=2.46, 95% (0.34, 18.06), p=0.376] and PFS [HR=2.60, 95% (0.68, 9.88), p=0.161]. There was statistically significant association between TLG and OS [HR=1.00, 95% (1.00, 1.00), p=0.00], while the HR was 1 so that the association could not be conclude, and TLG showed no association with PFS [HR=1.00, 95% (0.99, 1.00), p=0.974]. Conclusion High SUVmax indicates poor OS in patients with neuroblastoma. The MTV and TLG are potential prognostic predictors, which need to be further validated by more well-designed studies.